1991
DOI: 10.1128/mcb.11.1.182
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping elements in the guanylate-binding protein gene promoter mediate transcriptional induction by alpha and gamma interferons.

Abstract: The gene encoding a 67-kDa cytoplasmic guanylate-binding protein (GBP) is transcriptionally induced in cells exposed to interferon of either type I (alpha interferon [IFN-a] or INF-,) or type II (IFN--y 20,30,31). A DNA-binding protein termed ISGF-3 is responsible for the IFN-x-dependent activation through the ISRE. This conclusion is based on a variety of evidence, including the parallel induction of ISGF-3 and transcription even in the absence of ongoing protein synthesis (19,20), and on in vitro transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
201
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(203 citation statements)
references
References 37 publications
2
201
0
Order By: Relevance
“…The same nuclear extracts (40 mg) used for the EMSA shown in (b) and (c) were analysed for IRF-2 protein by Western blotting, as described in Materials and methods function in Hs766T (Figures 6 and 7) reduces but does not abolish IFN-g response of GBP gene ( Figure 8 and Table 1). The partial GBP induction by IFN-g could be attributable to activated STAT1, which binds to the GAS element overlapping with the IRF-E (Lew et al, 1991). A previous report indicated that the GAS element of the GBP promoter could function independently of IRF-E in the IFN-g response of GBP gene (Lew et al, 1991).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The same nuclear extracts (40 mg) used for the EMSA shown in (b) and (c) were analysed for IRF-2 protein by Western blotting, as described in Materials and methods function in Hs766T (Figures 6 and 7) reduces but does not abolish IFN-g response of GBP gene ( Figure 8 and Table 1). The partial GBP induction by IFN-g could be attributable to activated STAT1, which binds to the GAS element overlapping with the IRF-E (Lew et al, 1991). A previous report indicated that the GAS element of the GBP promoter could function independently of IRF-E in the IFN-g response of GBP gene (Lew et al, 1991).…”
Section: Discussionmentioning
confidence: 93%
“…The partial GBP induction by IFN-g could be attributable to activated STAT1, which binds to the GAS element overlapping with the IRF-E (Lew et al, 1991). A previous report indicated that the GAS element of the GBP promoter could function independently of IRF-E in the IFN-g response of GBP gene (Lew et al, 1991). Although the GAS element and STAT1 are also required for the IFN-g induction of the CIITA Type IV promoter (Muhlethaler-Mottet et al, 1998;Piskurich et al, 1999), recent evidence indicates that the CIITA Type IV promoter activation is more dependent on the IRF-E than the GAS element (Piskurich et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a number of promoters containing IRF-1 speci®c binding sites were tested for activation by IRF-1 and/or HER1. A construct containing a GAS (g-interferon activated sequence) element and the ISRE (interferon stimulated response Cooperation of HER and IRF-1 S Kirchhoff and H Hauser element) of the human GBP promoter (Lew et al, 1991; Figure 4a) was made. In addition, another promoter construct containing the consensus sequence of an ISRE (interferon stimulated regulatory element, Figure 4b) alone was used.…”
Section: Synergistic Activation Of Irf-1 Inducible Promoters By Irf-1mentioning
confidence: 99%